Combination of D0 measurements of the top quark mass - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Agnew, J. P.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Askew, A.; Atkins, S.; Augsten, K.; et al. (Amer Physical Soc, 2017)
We present a combination of measurements of the top quark mass by the D0 experiment in the lepton + jets and dilepton channels. We use all the data collected in Run I (1992-1996) at root s = 1.8 TeV and Run II (2001-2011) at root s = 1.96 TeV of the Tevatron p (p) over bar collider, corresponding to integrated luminosities of 0.1 fb(-1) and 9.7 fb(-1), respectively. The combined result is: m(t) = 174.95 +/- 0.40(stat)+/- 0.64(syst) GeV = 174.95 +/- 0.75 GeV.